TAXONOMIC STUDIES IN RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) (Acta Entomológica Chilena, 2022)
Rhagoletis tomatis Foote is a Chilean and Peruvian species of Tephritid fly which attacks fruits ofLycopersicum esculentum or tomate. This paper disccuses some taxonomic aspects of both immaturestages and adult flies. The results are important to differentiate R. tomatis from congeneric species.